Study on Challenges and Countermeasures for Deepening Scientific and Technological Innovation Cooperation under the Framework of China-EU "Belt and Road Initiative" Cooperation (Journal of Interdisciplinary Insights, 2025)
In the context of accelerating global technological innovation restructuring, Sino-European cooperation on scientific and technological innovation under the "Belt and Road Initiative" framework faces challenges such as complex geopolitical developments and divergent perceptions of China within the EU. However, it also harbors opportunities for collaboration in areas like green transition and digital economy. This paper, based on changes in the EU's "triple positioning" towards China and drawing on practical experiences from Germany's new energy transition, systematically reviews the current state of Sino-European cooperation on scientific and technological innovation. It delves into the main challenges currently faced and proposes policy recommendations from dimensions including building strategic trust, innovating cooperation mechanisms, achieving breakthroughs in key areas, and improving policy tools, aiming to provide theoretical references for promoting steady and sustainable progress in Sino-European cooperation on scientific and technological innovation.
Keywords: China-EU cooperation; "Belt and Road Initiative"; scientific and technological innovation